# Factorize x^2 - 8x + 12

### 2 Answers | Add Yours

We have to factorize : x^2 - 8x + 12

x^2 - 8x + 12

write -8 as the sum of 2 numbers which give a product 12. This can be done as -8 = -6 + -2

=> x^2 - 6x - 2x + 12

remove the common factor x in the first two terms and the common factor -2 in the last two terms

=> x(x - 6) - 2(x - 6)

remove the common factor (x - 6)

=> (x - 2)(x - 6)

**The factors of x^2 - 8x + 12 are (x - 2)(x - 6)**

The expression x^2 - 8x + 12 has to be factorized.

x^2 - 8x + 12

= x^2 - 6x - 2x + 12

= x(x - 6) - 2(x - 6)

= (x - 2)(x - 6)

The factorized form of x^2 - 8x + 12 = (x - 2)(x - 6)